Sealing type effect on corn silage quality in bunker silos - Neumann, Mikael (2017)
Forage conservation in silos depends on the efficiency of silo sealing, among other factors, to minimize aerobic deterioration and consequent qualitative and quantitative losses in silage. Thus, the aim of the present study was to evaluate the effect of two sealing types on dry matter recovery rate, aerobic stability, nutritional composition, and in vitro digestibility of corn silage in bunker silos: 110-mu m-thick double-sided polyethylene sealing (conventional sealing) and 110-mu m-thick double-sided polyethylene sealing superimposed on 111-mu m-thick translucent polyethylene sealing (double sealing). There were no significant differences in nutritional composition of silages between conventional and double sealing. However, the double sealing system was more efficient (P<0.05) in maintaining lower silo temperatures (30.48 degrees C vs. 31.18 degrees C), in dry matter recovery (88.79% vs. 85.64%), and increased in vitro neutral-detergent fiber digestibility (33.04% vs. 24.6%), when compared to the conventional version.